Anti-inflammatory and antibacterial activities of cerium-containing mesoporous bioactive glass nanoparticles for drug-free biomedical applications - Kurtuldu, Fatih; Kankova, Hana; Beltrán, Ana M.; Liverani, Liliana; Galusek, Dusan; Boccaccini, Aldo R. (Materials Today Bio, 2021)
Mesoporous bioactive glass nanoparticles (MBGNPs) are attracting significant attention as suitable materials for multifunctional biomedical applications. In this study, cerium was incorporated into MBGNPs using two different approaches. In the first approach, cerium was added to the glass system directly during the synthesis, while in the second approach, cerium was added to the as-synthesized MBGNPs via the template ion-exchange method. The influence of the method of synthesis on the physicochemical properties of nanoparticles was examined by SEM, TEM, XRD, FTIR, and N2 adsorption-desorption analyses. The MBGNPs exhibited spheroidal morphology and disordered mesoporous structure. XRD analysis confirmed the amorphous nature of the nanoparticles. The chemical composition was determined by the acid digestion method using ICP-OES. The influence of the synthesis method on the specific surface area, mesoporosity, and solubility of synthesized nanoparticles in Tris/HCl (pH 7.4) and acetate (pH 4.5) buffer has also been studied. The obtained Ce containing MBGNPs were non-cytotoxic toward ​preosteoblast MC3T3-E1 cells in contact with nanoparticles in a concentration of up to 100 ​μg/mL. The anti-inflammatory effect of Ce containing MBGNPs was tested with lipopolysaccharides (LPS)-induced proinflammatory RAW 264.7 macrophage cells. Ce containing MBGNPs decreased the release of nitric oxide, indicating the anti-inflammatory response of macrophage cells. Ce containing MBGNPs also showed antibacterial activity against S. aureus and E. coli. The mentioned features of the obtained MBGNPs make them useful in a variety of biomedical applications, considering their biocompatibility, anti-inflammatory response, and enhanced antibacterial effect.
Keywords: Metal ion; Bioactive glassses; Nanoparticles; Anti-inflammation activity; Antibacterial materials

Cerium and gallium containing mesoporous bioactive glass nanoparticles for bone regeneration: Bioactivity, biocompatibility and antibacterial activity - Kurtuldu, Fatih; Mutlu, Nurshen; Michálek, Martin; Zheng, Kai; Masar, Milan; Liverani, Liliana; Chen, Si; Galusek, Dušan; Boccaccini, Aldo R. (Materials Science and Engineering C, 2021)
In recent years, mesoporous bioactive glass nanoparticles (MBGNPs) have generated great attention in biomedical applications. In this study, cerium and gallium doped MBGNPs were prepared by microemulsion assisted sol-gel method in the binary SiO2-CaO system. MBGNPs with spheroidal and pineal shaped morphology were obtained. Nitrogen sorption analysis elucidated the mesoporous structure of synthesized nanoparticles with high specific surface area. X-ray diffraction analysis confirmed the amorphous nature of the nanoparticles. The chemical compositions of all samples were determined by inductively coupled plasma-optical emission spectrometry (ICP-OES), which revealed that the contents of cerium and gallium could be tailored by adjusting the concentrations of the precursors used for the synthesis. All MBGNPs exhibited in vitro bioactivity when immersed in simulated body fluid, except the particles doped with higher amounts than 1 mol% of cerium. MBGNPs showed antibacterial activity against S. aureus and E. coli without exhibiting cytotoxicity towards MG-63 osteoblast-like cells. Mentioned features of the obtained Ce and Ga-doped MBGNPs make them useful for multifunctional applications such as drug delivery carriers or bioactive fillers for bone tissue engineering applications.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Antibacterial activity; Cerium; Gallium; Mesoporous bioactive glass nanoparticles; Sol-gel method

Effect of Zn and Ga doping on bioactivity, degradation, and antibacterial properties of borate 1393-B3 bioactive glass - Mutlu, Nurshen; Kurtuldu, Fatih; Ünalan, Irem; Neščáková, Zuzana; Kaňková, Hana; Galusková, Dagmar; Michálek, Martin; Liverani, Liliana; Galusek, Dušan; Boccaccini, Aldo R. (Ceramics International, 2022)
Borate 1393-B3 bioactive glasses doped with ZnO or Ga2O3 (1, 3, and 6% mol) were produced by conventional melt quenching. All doped glasses showed in-vitro bioactivity in simulated body fluid (SBF). For the first time, the dissolution behavior of the glasses both in phosphate-buffered saline (PBS) and cell culture medium was investigated. The ion release rate in the cell culture medium increased compared to that in PBS solution. All tested glass compositions, including the parent 1393-B3 glass, showed antibacterial effect against S. aureus and E. coli. The incorporation of Zn and Ga enhanced the viability of MG-63 osteoblast-like cells compared to the base 1393-B3 glass. The results show the potential of Zn and Ga-doped borate glasses in multifunctional tissue engineering applications.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Antibacterial activity; Bioactive glasses; Borate glasses; Gallium; Zinc

Gallium containing bioactive materials: A review of anticancer, antibacterial, and osteogenic properties - Kurtuldu, Fatih; Mutlu, Nurshen; Boccaccini, Aldo R.; Galusek, Dušan (Bioactive Materials, 2022)
The incorporation of gallium into bioactive materials has been reported to enhance osteogenesis, to influence blood clotting, and to induce anti-cancer and anti-bacterial activity. Gallium-doped biomaterials prepared by various techniques include melt-derived and sol-gel-derived bioactive glasses, calcium phosphate bioceramics, metals and coatings. In this review, we summarize the recently reported developments in antibacterial, anticancer, osteogenesis, and hemostasis properties of Ga-doped biomaterials and briefly outline the mechanisms leading to Ga biological effects. The key finding is that gallium addition to biomaterials has great potential for treating bone-related diseases since it can be efficiently transferred to the desired region at a controllable rate. Besides, it can be used as a potential substitute for antibiotics for the inhibition of infections during the initial and advanced phases of the wound healing process. Ga is also used as an anticancer agent due to the increased concentration of gallium around excessive cell proliferation (tumor) sites. Moreover, we highlight the possibility to design different therapeutic approaches aimed at increasing the efficiency of the use of gallium containing bioactive materials for multifunctional applications.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Antibacterial; Bioactive materials; Cancer treatment; Hemostasis; Osteogenesis

Gallium-containing mesoporous nanoparticles influence in-vitro osteogenic and osteoclastic activity - Kurtuldu, Fatih; Mutlu, Nurshen; Friedrich, Ralf P.; Beltrán, Ana M.; Liverani, Liliana; Detsch, Rainer; Alexiou, Christoph; Galusek, Dušan; Boccaccini, Aldo R. (Biomaterials Advances, 2024)
Mesoporous silica nanoparticles were synthesized using a microemulsion-assisted sol-gel method, and calcium, gallium or a combination of both, were used as dopants. The influence of these metallic ions on the physicochemical properties of the nanoparticles was investigated by scanning and transmission electron microscopy, as well as N2 adsorption-desorption methods. The presence of calcium had a significant impact on the morphology and textural features of the nanoparticles. The addition of calcium increased the average diameter of the nanoparticles from 80 nm to 150 nm, while decreasing their specific surface area from 972 m2/g to 344 m2/g. The nanoparticles of all compositions were spheroidal, with a disordered mesoporous structure. An ion release study in cell culture medium demonstrated that gallium was released from the nanoparticles in a sustained manner. In direct contact with concentrations of up to 100 μg/mL of the nanoparticles, gallium-containing nanoparticles did not exhibit cytotoxicity towards pre-osteoblast MC3T3-E1 cells. Moreover, in vitro cell culture tests revealed that the addition of gallium to the nanoparticles enhanced osteogenic activity. Simultaneously, the nanoparticles disrupted the osteoclast differentiation of RAW 264.7 macrophage cells. These findings suggest that gallium-containing nanoparticles possess favorable physicochemical properties and biological characteristics, making them promising candidates for applications in bone tissue regeneration, particularly for unphysiological or pathological conditions such as osteoporosis.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Bioactive glasses; Gallium; Mesoporous silica nanoparticles; Osteoblast; Osteoclast

Impact of morphological features and chemical composition of tendon biomimetic scaffolds on immune recognition via Toll-like receptors - Gil-Cantero, Sara; Iorio, Francesco; Ünalan, Irem; Kurtuldu, Fatih; Künig, Sarojinidevi; Wenhardt, Claus; Pinnaro′, Veronica; Aigner-Radakovics, Katharina; Steinberger, Peter; Boccaccini, Aldo R.; Stöckl, Johannes (Biomaterials Science, 2024)
Tendinopathies are a major worldwide clinical problem. The development of tendon biomimetic scaffolds is considered a promising, therapeutic approach. However, to be clinically effective, scaffolds should avoid immunological recognition. It has been well described that scaffolds composed of aligned fibers lead to a better tenocyte differentiation, vitality, proliferation and motility. However, little has been studied regarding the impact of fiber spatial distribution on the recognition by immune cells. Additionally, it has been suggested that higher hydrophilicity would reduce their immune recognition. Herein, polycaprolactone (PCL)-hyaluronic acid (HA)-based electrospun scaffolds were generated with different fiber diameters (in the nano- and micro-scales) and orientations as well as different grades of wettability and the impact of these properties on immunological recognition has been assessed, by means of Toll-like receptor (TLR) reporter cells. Our results showed that TLR 2/1 and TLR 2/6 were not triggered by the scaffolds. In addition, the TLR 4 signalling pathway seems to be triggered to a greater extent by higher PCL and HA concentrations, but the alignment of the fibers prevents the triggering of this receptor. Taken together, TLR reporter cells were shown to be a useful and effective tool to study the potential of scaffolds to induce immune responses and the results obtained can be used to inform the design of fibrous scaffolds for tendon repair.
CRIS-Team Scopus Importer:2024-08-23

Morphology and topography of chitosan-Zn complex/PEO fiber mats influence cell viability and attachment - Mutlu, Nurshen; Kurtuldu, Fatih; Nowicka, Aleksandra; Liverani, Liliana; Galusek, Dušan; Boccaccini, Aldo R. (International Journal of Biological Macromolecules, 2025)
Electrospun fiber mats with therapeutic potential show great promise as wound healing biomaterials. This study aims to compare the biophysical properties and biocompatibility of four different biodegradable fiber mats; namely chitosan and chitosan‑zinc complex (ChiZn)/(polyethylene oxide) PEO fibers, each with either nanometer-sized ( 200 nm) or micron-sized ( 1000 nm) diameters. Zn was incorporated to impact antibacterial properties of the fibers, ChiZn was synthesized using the in-situ precipitation method, and the influence of zinc chelation on the material structure and morphology was assessed using XRD, FTIR, XPS, and EDX, documenting the complexation and homogeneous distribution of zinc. ChiZn was then blended with PEO for electrospinning in a benign solvent system and crosslinked with glutaraldehyde vapor. SEM was used to examine fiber morphology while AFM documented a correlation between the roughness and fiber diameter. The effects of topography and composition on the viability, adhesion, and proliferation of stromal cells and mouse fibroblasts were investigated, showing higher cell viability on mats composed of nanosized fibers, whereas complex fiber mats composed of micron-sized fibers exhibited reduced cell viability. SEM evaluations showed that cells spread only on the surface of the nanosized fibers, independently of the presence of Zn, while cell infiltration into the mats was observed for micron-sized fibers.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Chitosan; Complexation; Electrospinning

Zinc improves antibacterial, anti-inflammatory and cell motility activity of chitosan for wound healing applications - Mutlu, Nurshen; Liverani, Liliana; Kurtuldu, Fatih; Galusek, Dušan; Boccaccini, Aldo R. (International Journal of Biological Macromolecules, 2022)
We report the successful preparation and characterization of chitosan-Zn complex (ChiZn) in the form of films, intended to enhance the biological performance of chitosan by the presence of Zn as antibacterial agent and biologically active ion. The influence of Zn chelation on morphology and structure of chitosan was assessed by scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy and infrared spectroscopy. The biodegradability study of ChiZn showed a sustained release of Zn up to 2 mg/mL. No toxic response was observed toward stromal cell line ST-2 in indirect contact with the ChiZn films. The dissolution product of ChiZn showed improved wound closure (88% closure) compared to the positive control group (70% closure). Moreover, ChiZn exhibited antibacterial activity against S. aureus together with a slight increase ( 30%) in the secretion of VEGF and moderate decrease in nitric oxide evolution. Our findings indicate that ChiZn could be used as a safe and effective wound healing agent.<br
Keywords: Chitosan‑zinc complex; Chelation process; Wound healing; Antibacterial activity